Preparation and electrochemical properties of NiCo2O4 nanorods grown on nickel foam filled by carbon-coated attapulgite for supercapacitors. (4th December 2019) - Wang, Qi; Liu, Xindong; Ju, Tao; Ying, Zongrong; Xie, Jie; Zhang, Yongzheng
Abstract: The nickel-foam(NF)-based binder-free electrode has attracted much attention recently. Common method is to grow directly nanostructured active materials on the skeleton surface of NF substrate for developing advanced electrode materials. However, few attempts have been reported to enlarge the NF loading area for improving electrochemical performance to date. Herein, we employed nanofibrous attapulgite coated by N-doped carbon (ANC) to adhere onto the skeleton and inside the meshes of NF for enlarging loading area, and then grown NiCo2 O4 nanorods on the filled NF via a hydrothermal process. The as-synthesized samples were evaluated as supercapacitor electrodes and demonstrate excellent electrochemical performances with a high areal specific capacitance (3.41 F cm −2 at 1 mA cm −2 ), much higher than that of NiCo2 O4 nanorods grown on raw nickel foam (1.52 F cm −2 at 1 mA cm −2 ), as well as a good rate capacity and cycling stability. This work provide a simple effective method for fabricating high-performance NF-based binder-free electrodes in energy-storage devices.